Ethno-medicinal Uses of Animals and Plants among the Migratory Tangbetons of Pokhara, Nepal - Paudyal, Ranju; Singh, N.B. (Journal of Institute of Science and Technology, 2015)
This paper attempts to study various uses of medicinal animals and plants among the migratory Tangbetons of Nepal who were migrated to Pokhara Sub-Metro Politian City from Tangbe Village in Mustang district. Direct observation, questionnaire survey and key informant interview were conducted during the study period. Information about the medicinal plants and animals were given mainly by the Amchi and their information was taken from the elder persons. Finally, this paper recorded 17 medicinal animal species and 60 widely used medicinal plant species for the treatment of various diseases. Journal of Institute of Science and Technology, 2014, 19(1): 145-149